2019
DOI: 10.1097/md.0000000000015130
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in stroke patients and risk factors associated with patients for return to work

Abstract: To clarify dynamic change of quality of life (QOL) in patients with stroke after treatment, and to explore the predictors associated with return to work (RTW) within 48 weeks. Patients diagnosed with stroke were enrolled. All patients enrolled were asked to fill in the Short Form 36 Health Survey. For patients with stroke, SF-36 questionnaires were measured repeatedly 4 weeks after treatment. We used phone call to find out if the patient was RTW. The investigation time was 48 weeks. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
5
44
1
3
Order By: Relevance
“…Only the level of education was found to considerably affect OHR-QoL. In contrast to previous studies, 27,28 those with higher education levels in this study usually reported a lower level of OHR-QoL. This trend could emanate from the individuals' expectations when evaluating their OHR-QoL.…”
Section: Discussioncontrasting
confidence: 91%
“…Only the level of education was found to considerably affect OHR-QoL. In contrast to previous studies, 27,28 those with higher education levels in this study usually reported a lower level of OHR-QoL. This trend could emanate from the individuals' expectations when evaluating their OHR-QoL.…”
Section: Discussioncontrasting
confidence: 91%
“…For those neurological outcomes that can produce long-term complications, such as stroke and encephalitis which may seriously affect the patient's later quality of life [ 58 ], more studies on the risk factors of such complications, in the form of population-based studies with larger sample size and longer follow-up time are needed.…”
Section: Narrative Reviewmentioning
confidence: 99%
“… 4 5 In addition, the risk of disability by stroke was higher than myocardial infarction. 4 The prevalence of stroke leads to poor quality of life, 6 7 economic burden from medical expense, 8 and high burden of disease 9 and disability. 10 Ultimately, it negatively affects both countries and individuals.…”
Section: Introductionmentioning
confidence: 99%